Sexual offending and mental health : multidisciplinary management in the community - Houston, Julia; Galloway, Sarah (Forensic focus ;, 2008)
Sexual Offending and Mental Health draws together theoretical, clinical and mental health issues for the range of professionals working in the community and in-patient settings with sex offenders and those who have behaved in sexually inappropriate ways. The contributors describe current influential models of sexual offending and the developmental, psychological and social factors involved. They discuss the prevalence of personality and mental disorders in known sex offenders and the impact these disorders have on their treatment and management. They describe clinical work with individuals, th.